Evaluation of Total Antioxidant Activity and Total Phenolic Content of Different Tahini (Sesame Paste) Brands in Iran’s Market - Naficeh Sadeghi (Medical Laboratory Journal, 2020)
Background: Tahini (sesame paste) is a kind of food obtained from sesame seeds. To our knowledge, this is the first study to measure total antioxidant activity and total phenolic compounds in tahini brands available in Iranian market. Methods: In this study, 111 tahini samples were collected and purchased from the Iranian Market, including 37 commercial brands (three samples for per brand). The ferric reducing ability of plasma (FRAP) method was used to measure total antioxidant activity in each sample. Total phenol contents were measured by the Folin–Ciocalteau method in tahini brands. Results: Current study showed Mino-dates brand (119.93 µmol/ml ±0.159), Trang-Chocolate brand (56.30 µmol/ml ±0.056), Barsam-coffee (45.13µmol/ml±0.094), and Chocolate-barsam brand (53.23 µmol/ml ±0.112), respectively, have more total antioxidant activity than other brands (p< 0.001). Moreover, Mino-dates brand (2057.33 µmol/ml ±0.094), barsam-coffee (805.51 µmol/ml ±0.041), Chocolate-barsam brand (807.42 µmol/ml ±0.095), and Trang-Chocolate brand (685.75 µmol/ml ±0.086), respectively, have more total phenolic compounds than other brands (p< 0.001). Conclusion: According to the results of this study, Tahini brands with higher polyphenol contents antioxidant capacity also had higher antioxidant capacity. It can be concluded that Tahini in the Iranian market is one of the most valuable foods in terms of antioxidant activity and total phenolic contents.